PROMOSI OBJEK WISATA OLEH DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KAMPAR, PROVINSI RIAU - Mariaty Ibrahim; Musadad Musadad (Jurnal Pariwisata Pesona, 2021)
This study was aimed at examining the promotional activities performed by the Tourism of Office of Kampar Regency and to identify the challenges in promoting tourism in Kampar Regency. This qualitative study collected data through interviews with two key informants, namely the Head of Marketing Department and the Head of the Promotion Section. The data was also collected through document review as the secondary data. The analysis results indicate that the promotional activities carried out by the Kampar Regency Tourism Office includes above-the-line and below-the-line media but the promotion through above-the-line media is still very simple. Thus, a more varied promotional media such as digital technology or self-managed websites is needed so that information coverage for the public, investors and tourists will be faster and wider. Moreover, the main challenge for the promotional activities by the Kampar Tourism Office is the lack of annual budgets.